Development of Elisa for the detection of Ralstonia solanacearum in tomato: its application in seed health testing - Rajeshwari, N.; Shylaja, M.D.; Krishnappa, M.; Shetty, H.S.; Mortensen, C.N.; Mathur, S.B. (Copenhagen (Dinamarca), 1998)
Sumario (En)
36 ref.
Keywords: VIROSIS; BACTERIORIS; PSEUDOMONAS SOLANACEARUM